Performance Evaluation in Public Information Services in General Election Commission Tanjung Jabung Timur Regency - Putri, Nafa Yulianti; Sumarni, Sumarni; Aira, Dian Mala Fitriani (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study evaluates the performance of public information services at the General Election Commission (KPU) of East Tanjung Jabung Regency. Public information is vital for good governance and transparency in electoral processes. Using a qualitative case study method, data were collected through interviews with KPU officials and staff, along with direct observations. The results show that overall service performance is effective in supporting democratic elections. However, weaknesses remain in empathetic service delivery and equitable access in underdeveloped areas. The study recommends capacity building, budget efficiency, and inclusive communication strategies to enhance service quality.